Unresponsiveness to skin testing with bacterial antigens in patients with haemophilia A not apparently infected with human immunodeficiency virus (HIV). Issue 8 (August 1987) - Sharp, R A; Morley, S M; Beck, J S; Urquhart, G E
Abstract : Unresponsiveness to skin testing with PPD and tetanus toxoid was commonly seen in patients with haemophilia A but not infected with human immunodeficiency virus but was uncommon in controls. Vaccination history indicated that the unresponsive patients had not been immunised in childhood. Other tests of immune competence (skin tests with other antigens, lymphocyte stimulation with mitogens and antigens, and viral serology) showed that the haemophilia A patients had an adequate response to pathogens to which they had been exposed. Five of 12 such patients had a mild T4 lymphopenia, and this may have been related to parenteral administration of large quantities of protein.